Shoot flammability is decoupled from leaf flammability, but controlled by leaf functional traits. (8th October 2019) - Alam, Md Azharul; Wyse, Sarah V.; Buckley, Hannah L.; Perry, George L. W.; Sullivan, Jon J.; Mason, Norman W. H.; Buxton, Rowan; Richardson, Sarah J.; Curran, Timothy J.
Abstract: Flammability is an important plant trait, relevant to plant function, wildfire behaviour and plant evolution. However, systematic comparison of plant flammability across ecosystems has proved difficult because of varying methodologies and assessment of different fuels comprising different plant parts. We compared the flammability of plant species at the leaf‐level (most commonly used in flammability studies) and shoot‐level (which retains aspects of plant architecture). Furthermore, we examined relationships between leaf functional traits and flammability to identify key leaf traits determining shoot‐level flammability. We collated and analysed existing leaf‐ and shoot‐level flammability data from 43 common indigenous perennial New Zealand plant species, along with existing data on leaf morphological and chemical traits. Shoot‐level flammability was decoupled from leaf‐level flammability. Moreover, leaf‐level rankings of flammability were not correlated with rankings of flammability of plants derived from expert opinion based on field observations, while shoot‐level rankings had a significant positive relationship. Shoot‐level flammability was positively correlated with leaf dry matter content (LDMC), phenolics and lignin, and negatively correlated with leaf thickness. Synthesis . Our study suggests that shoot‐level measurements of flammability are a useful and easily replicable way of characterizing the flammability of plants, particularly canopy flammability. With many parts of the world becoming more fire‐prone, due to anthropogenic activities, such as land‐use change and global warming, this finding will help forest and fire managers to make informed decisions about fuel management, and improve modelling of fire‐vegetation‐climate feedbacks under global climate change. Additionally, we identified some key, widely measured leaf traits, such as leaf dry matter content (LDMC), that may be useful surrogates for plant flammability in global dynamic vegetation models. Abstract : Shoot‐ and leaf‐level flammability were decoupled, and shoot flammability corresponded to rankings based on expert opinion, suggesting that shoot‐level tests are a useful way to characterize the flammability of canopy fuels. Furthermore, we identified some widely measured leaf traits, such as leaf dry matter content, that were highly correlated to shoot flammability and can be useful surrogates for measuring plant flammability.